PENGARUH KARAKTERISTIK PERUSAHAAN DAN CORPORATE GOVERNANCE TERHADAP INTELLECTUAL CAPITAL DISCLOSURE SERTA DAMPAKNYA TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Perbankan Yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018) - Riyani Morin; Linda Y. Hutadjulu; Aaron M. A Simanjuntak (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2019)
This study aims to analyze the influence of firm characteristics and corporate governance on intellectual capital disclosure and its impact on firm value. This research was conducted again to review the inconsistency of the diversity of the results of previous studies. Firm characteristics are proxied with corporate governance as an independent variable in this study, intellectual capital disclosure is an intervening variable, and firm value as the dependent variable. The results of this study show that firm size has influence on the intellectual capital disclosure. Leverage, profitability, board independence, audit committee, board size do not have influence on intellectual capital disclosure. Intellectual capital disclosure does not have influence on firm value.